The Role of Dialogical Patrol of the Samapta Unit Patrol Unit in Preventing Motor Vehicle Theft in Surabaya Polrestabes - Hizqya, Mochamad Alif (Advances in Police Science Research Journal, 2024)
The city of Surabaya, as one of the largest cities in Indonesia, has complex social and economic dynamics. In the midst of rapid economic growth and high community mobility, the city of Surabaya also faces serious challenges in terms of security, especially related to the problem of motor vehicle theft. Motor vehicle theft is one of the criminal problems that worries Surabaya residents and has a significant economic impact. The aim of this research is to describe dialogic patrol efforts and what factors hinder the role of dialogic patrols carried out by the Surabaya Police Samapta Unit in preventing an increase in cases of motor vehicle theft. The research method used is a qualitative research method. The results of the research show that the dialogic patrol effort carried out by the Surabaya Police Samapta unit in dealing with theft cases is implementing a dialogic patrol strategy which involves active interaction between patrol officers and the community. Factors hampering the role of the ideological patrol of the Surabaya Police Samapta unit in dealing with cases of theft are hampered by limited members, lack of ability of members to carry out their duties, lack of budget for patrol vehicle’s fuel, and lack of patrol implementation optimization. This results in patrols not being able to be carried out optimally, providing opportunities for criminals to take action, and increasing the crime rate in the area.